Radar-measurements in the Tropo, Strato and Mesosphere - Rüster, R. (1976)
An experiment was performed using the large 50 MHz-radar at Jicamarca/ Peru to obs erve waves, winds and clear air turbulence (CAT) at tropospheric and stratospheric heights. The antenna was used asan interferometer in order to measure the scale size of the turbulent inhomogeneities and to obtain velocities in an alternative way (other than Doppler). The scale size of the inhomogeneities is one of the important parameters in designing the Harz-VHF-radar facility. The various measurements, the data evaluation as well as first results are discussed.